The Influence of Self-Esteem toward Self-Adjustment - Fajar Wahyu Prasetyo; Diana Septi Purnama; Arif Budi Prasetya (Universitas Ahmad Dahlan, 2020)
This study aims to identify the effect of self-esteem on student self-adjusment. The research involved a sample of 210 students of grade X State Senior High School (SMAN) 1 Bangil Pasuruan that were randomly selected. The data analysis technique used in this study is regression analysis. The result showed that there was a significant influence between self-esteem on student self-adjusment. This study recommends a counseling service to improve student self-adjusment by involving self-esteem variables.